Antibacterial effect of hydroethanolic Annona muricata leaf extract against Streptococcus sanguinis ATCC 10556: an in vitro study - Alan Patricio Isique-Quesquen; Ruth Nerina Domínguez-Aburto (TUMI Oral Health, 2026)
Introduction: The increasing interest in plant-derived antimicrobial compounds has encouraged the evaluation of Annona muricata as a potential source of bioactive substances against oral microorganisms. Streptococcus sanguinis is an early colonizer of dental biofilm and may participate in the establishment of complex oral microbial communities. Objective: To evaluate the in vitro antibacterial activity of three concentrations of hydroethanolic Annona muricata leaf extract against Streptococcus sanguinis ATCC 10556. Methods: An experimental in vitro study was conducted using hydroethanolic leaf extract at concentrations of 50%, 75%, and 100%, with eight replicates per group. Chlorhexidine 0.12% and ethanol 70% were used as positive and negative controls, respectively. Antibacterial activity was evaluated by agar disk diffusion, and inhibition-zone diameters were measured in millimeters. Differences among groups were assessed using the Kruskal–Wallis test. Results: Mean inhibition-zone diameters were 6.63 ± 0.52 mm, 13.06 ± 0.30 mm, and 16.44 ± 0.37 mm for the 50%, 75%, and 100% extracts, respectively. Chlorhexidine produced the largest inhibition zone (21.55 ± 1.23 mm), whereas ethanol produced 6.00 ± 0.00 mm. Overall differences among groups were statistically significant (p < 0.001). Conclusions: Hydroethanolic Annona muricata leaf extract exhibited concentration-dependent in vitro antibacterial activity against S. sanguinis ATCC 10556, with the greatest activity observed at 100%, although chlorhexidine showed the highest inhibitory effect.